Factors associated with occult lateral lymph node metastases in patients with clinically lymph node negative papillary thyroid carcinoma: a systematic review and meta-analysis - Fei, Yuan; Wang, Bin; Yao, Xinmin; Wu, Jian (Frontiers in Endocrinology, 2024)
Background It remains unclear which category of patients with clinically lymph node negative (cN0) papillary thyroid carcinoma (PTC) might have higher risk of occult lateral lymph node metastasis (OLLNM) due to the conflicting results in previous studies. This systematic review and meta-analysis aimed to investigate factors associated with OLLNM in patients with cN0 PTC. Methods PubMed, EMBASE, Cochrane Library and Web of Science were comprehensively searched by two independent investigators to 15 August 2022. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for the pooled analysis. This systematic review and meta-analysis was registered in PROSPERO (CRD42022353567). Results Fifteen eligible studies involving 8369 patients with cN0 PTC were included in this meta-analysis. We found 7 factors significantly associated with OLLNM, including male (OR, 1.47; 95% CI, 1.30 to 1.66; P < 0.001), age<45y (OR, 1.65; 95% CI, 1.31 to 2.06; P < 0.001), tumor size > 10mm (OR, 3.17; 95% CI, 2.04 to 4.93; P <0.001), tumor located in upper pole (OR, 1.81; 95% CI, 1.44 to 2.27; P <0.001), bilaterality (OR, 1.66; 95% CI, 1.37 to 2.02; P <0.001), extrathyroidal extension (ETE) (OR, 2.52; 95% CI, 1.72 to 3.68; P <0.001) and increased number of central lymph node metastasis (CLNM) (OR, 6.84; 95% CI, 5.66 to 8.27; P <0.001). The results of sensitivity analysis and subgroup analysis were similar to the pooled results. No significant publication bias was observed. Conclusions The systematic review and meta-analysis identified 7 factors associated with OLLNM in patients with cN0 PTC. Future studies are needed to validate our results. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42022353567.